Land Use Analysis and Direction for Land Use Plan to Support Regional Development of Seluma Regency, Bengkulu Province - Hendra Saputra; Santun R. P. Sitorus; Indarti Komala Dewi (Riviera Publishing, 2024)
Regional inequality in Bengkulu Province is getting higher with regional expansion. This regional inequality is visible in Seluma Regency. Therefore, Seluma Regency must maximize its economic potential by optimizing the agricultural sector. This can be done by developing land-based areas through appropriate land use according to the potential of land for agriculture. The objectives of this research are 1) to analyze land use changes, 2) to analyze the suitability of land use to capability land for agricultural commodities, 3) to analyze the suitability of land use to the spatial patterns, and 4) to prepare land use plans to support regional development plans. This research uses quantitative data consisting of primary data and secondary data. The research was conducted using spatial analysis in Seluma Regency, Bengkulu Province. The research results show that 1) land use changes are dominated by an increase of rice fields, dry/wetland forests, and open land area, 2) suitability of land use to capability land for agricultural commodities is 39.77%, and 4.02% is still possible to adjust to capability land for agricultural commodities, 3) suitability of land use to the spatial pattern is 55.10% and 5.65% is still possible to be adjusted to spatial pattern (transition), and 4) land use plans to support regional development are directed as an agricultural area with an area of 45.11% of Seluma Regency total area.